High-Dose Rate Brachyther-apy in the Treatment of Early Stages of Penile Carcinoma - Pohanková, D; Sirák, I; Kašaová, L; Grepl, J; Paluska, P; Louda, M; Holub, L; Špaček, J; Prošvic, P; Petera, J (Klinicka onkologie, 2019)
BACKGROUND: Interstitial low dose rate brachyther-apy is established organ spar-ing treatment of T1- T2 penile carcinoma. Experience with high-dose rate brachyther-apy is limited in this indication. MATERIALS AND METHODS: Twenty-six patients with early penile carcinoma were treated by high-dose rate brachyther-apy at dose 18 × 3 Gy per fraction twice daily between 2002- 2018 at the Department of Oncology and Radiother-apy, University Hospital in Hradec Kralove. Breast interstitial brachyther-apy template was used for fixation and precise geometry reconstruction of stainless hollow needles. RESULTS: Median follow up was 85 months (range 7- 200 months). Acute reaction usually consisted of grade 2 mucositis that dissolved dur-ing 8 weeks after the treatment. Local recurrence occurred in 6 patients, 5 of them were successfully treated with partial amputation. One patient had a nodal recurrence successfully salvaged by lymphadenectomy. One patient developed necrosis of the glans requir-ing partial amputation. Currently, there are 24 patients alive without signs of dis-ease. One patient died of cardiac comorbidity, one died of duplicate lung cancer. Nineteen patients have a preserved penis (73%), 18 of them sexually active before treatment report satisfactory intercourse. CONCLUSION: Hyperfractionated interstitial high-dose rate brachyther-apy with 18 × 3 Gy per fraction twice daily is a promis-ing method in selected patients with penile carcinoma and deserves further evaluation in a larger prospective study. Key words penile neoplasms -  conservative treatment -  brachyther-apy This work was supported by programm Progres Q40. The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 8. 1. 2019 Accepted: 15. 1. 2019.
Keywords: Humans; lidé středního věku; or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 8. 1. 2019 Accepted: 15. 1. 2019; products; Aged; dospělí; výsledek terapie; Penile Neoplasms; senioři; lidé; nádory penisu; Adult; Male; Middle Aged; Treatment Outcome; mužské pohlaví; penile neoplasms - conservative treatment - brachytherapy This work was supported by programm Progres Q40. The authors declare they have no potential conflicts of interest concerning drugs; brachyterapie; Brachytherapy